Daya Tetas Telur Itik Cihateup dan Alabio - Darmawati, D.; Rukmiasih, Rukmiasih; Afnan, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Local ducks in Indonesia such as alabio duck and cihateup duck have advantages as egg producer and meat producer. Efforts is needed to increase the population of ducks by doing hatching. This research is to learn the hatchability of alabio duck and cihateup duck and identify of the factors that can be affected hatching duck eggs. Eggs ducks used 200 grains eggs ducks cihateup and eggs ducks alabio 300 grains. The process of hatching the egg ducks held for 28 days. The percentage fertility and hatchability results duck eggs alabio higher than cihateup duck eggs. Death embryonic the biggest occurred on the day to 26-28 days. Greater egg weights produce larger DOD. Weight of eggs and duck eggs index has no effect on hatchability but which affect hatchability of duck eggs in this study is high temperature during incubation, lower humidity during the period hatcher and egg hygiene. Alabio duck egg weight is lighter than duck eggs cihateup and more oval shaped while cihateup duck eggs more rounded shape. Weight egg and index egg on two types of eggs uniforms.